2018
DOI: 10.7717/peerj.5204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of clonal lineage and staphylococcal toxin genes fromS. aureusin Southern Nigeria

Abstract: BackgroundStaphylococcus aureus is a human colonizer with high potential for virulence, and the spread of the virulent strains from the colonized hosts to non-carriers in the community is on the increase. However, there are few reports on comprehensive analysis of staphylococcal enterotoxin (SE) genes with clonal lineage in S. aureus in Africa. This is essential because of diversity of cultures and habits of the people. This study analyzed spa types and enterotoxin genes in S. aureus strains previously isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(58 reference statements)
2
4
0
Order By: Relevance
“…There was the same proportion between sei and seg in our study. Previous studies have indicated associations between seg and sei , in which the most frequent SE genes detected in different locations were seg/sei , as reported in other countries ( Loncarevic et al, 2005 ; Kolawole et al, 2013 ; Ayeni et al, 2018 ). seg and sei were frequently encountered together because they were within the same cluster in a 3.2-kb DNA fragment ( Asiimwe et al, 2017 ).…”
Section: Discussionsupporting
confidence: 69%
“…There was the same proportion between sei and seg in our study. Previous studies have indicated associations between seg and sei , in which the most frequent SE genes detected in different locations were seg/sei , as reported in other countries ( Loncarevic et al, 2005 ; Kolawole et al, 2013 ; Ayeni et al, 2018 ). seg and sei were frequently encountered together because they were within the same cluster in a 3.2-kb DNA fragment ( Asiimwe et al, 2017 ).…”
Section: Discussionsupporting
confidence: 69%
“…Here, all the strains examined possessed at least one staphylococcal enterotoxin gene with seo being the most prevalent gene. This agreed with the results of [20] obtained in Algeria. This is a high occurrence with public health implications as staphylococcal enterotoxins can induce T-cell stimulation, resulting in systemic illness such as toxic shock syndrome and food poisoning.…”
Section: Discussionsupporting
confidence: 93%
“…Functional agr groups were reported to enhance persistent staphylococci bacteraemia and soft tissue tropism with low antibiotic susceptibility to penicillin, cephalosporin and vancomycin [ 7 , 8 ]. Similar clonal spread of MRSA (methicillin-resistant Staphylococcus aureus ) and MSSA (methicillin-susceptible Staphylococcus aureus ) is becoming pandemic in several communities in Africa, mostly Nigeria where animal husbandry, behavioural responses and declined demographic factors enhance continuous dissemination of staphylococcal infection with high degree of antibiotic resistance [ 9 ]. The misuse and unregulated prescription of penicillin derivatives in high and uncontrollable proportion for treating several extra-intestinal infections such as abscess, ear infections, subcutaneous tissue inflammation, nasal discharges particularly in children and post-surgical wound culminated in a high rate of resistance and continuous development of methicillin-resistance strains [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%